An extrapolation method for polarisability assessments of ion-based optical clocks - M D Barrett; K J Arnold (New Journal of Physics)
We present a numerical method for extrapolating polarisability measurements to dc as sometimes done in the assessment of blackbody radiation shifts for ion-based optical clocks. The method explicitly accounts for the frequency dependence of relevant atomic transitions without introducing an ad hoc modelling function. It incorporates a priori atomic structure calculations, which allows measurements to be augmented by calculations if there is insufficient data to make a purely measurement based estimate. The method also provides indicators of inconsistencies between theory and experiment or inadequacies of the data for making an extrapolation. We apply the method to Al ^+ , Lu ^+ , and Yb ^+ for the purposes of illustration.